2019
DOI: 10.1093/jpids/piz019
|View full text |Cite
|
Sign up to set email alerts
|

Outsourcing Microbiology Services in Medical Centers: Is It Worth It?

Abstract: Background Outsourcing of microbiology laboratory services is a growing trend in US medical centers. Data on the actual impact of outsourcing on patient care, safety, and medical education, including costs, are limited. The objective of this study was to examine the published literature on the potential benefits and harms when medical centers outsource common microbiology services. Methods We conducted a 16-step literature se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…5,53 More than 85% of infectious disease physicians report that having laboratory services onsite is crucial for timely diagnosis, care coordination, and communication with clinical microbiologists. 54 In a prospective study on the use of blood cultures, hospitals with offsite lab services experienced significantly longer transport times and total detection times for the presence of 12 different species of sepsiscausing bacteria and yeasts. 55 A study reporting interviews with 17 pathology department chairs at US academic medical centers revealed that the institutions that entered into joint ventures with lab service providers experienced unplanned, sizable cost increases over time, even though the primary reason for initiating the venture was financial.…”
Section: Laboratory Servicesmentioning
confidence: 99%
“…5,53 More than 85% of infectious disease physicians report that having laboratory services onsite is crucial for timely diagnosis, care coordination, and communication with clinical microbiologists. 54 In a prospective study on the use of blood cultures, hospitals with offsite lab services experienced significantly longer transport times and total detection times for the presence of 12 different species of sepsiscausing bacteria and yeasts. 55 A study reporting interviews with 17 pathology department chairs at US academic medical centers revealed that the institutions that entered into joint ventures with lab service providers experienced unplanned, sizable cost increases over time, even though the primary reason for initiating the venture was financial.…”
Section: Laboratory Servicesmentioning
confidence: 99%
“…Generally, the conducted researches show that although various models exist to outsource services however, this capacity has not been fully utilized and in most cases one or two models have been considered by policy makers and managers. Low motivation and tendency of managers, lack of complete understanding of outsourcing philosophy, unfamiliarity of managers with common outsourcing models, unsuccessful experiences of outsourcing, lack of eligible private provider and weakness in law and regulation are factors that have hindered outsourcing expansion (Mujasi & Nkosi, 2019;Penton et al, 2020;Shaarbafchizadeh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Given this, the public sector could improve the efficiency and quality of delivered services due to exposure to a competitive condition. The more competitive a market is, the higher the efficiency and quality of services will be (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%